SOCIOECONOMIC DETERMINANTS OF GENDER DIFFERENCES IN SELF-REPORTED HEALTH STATUS AMONG OLDER POPULATION - Ilic, Sladjana; Radevic, Svetlana R; Janicijevic, Katarina; Miljanovic, Ana; Andric, Dragana; Ikovic, Majda; Pantovic, Milica (Sanamed, 2022)
Introduction: Self-reported health status is considered one of the highly significant indicators of general health and overall quality of life.Aim: to examine whether there are gender differences in self-reported health status among the older population depending on the socioeconomic determinants.Methods: The analysis was carried out based on the data collected from the fourth National Health Survey of the population of Serbia, which was designed as a cross-sectional study. The research was conducted in accordance with the methodological guidelines and research instruments of the European Health Interview Survey.Results: A statistically significant correlation was observed between gender and the self-reported health status of the respondents. Women were significantly more likely to report poor self-rated health (27.8%), whereas men reported better self-rated health (21.3%). The results of the multivariate logistic regression analysis showed that poor self-rated health status among women was more likely to be affected by age, educational level, and region, whereas age and economic status were significant factors associated with poor self-rated health status among men.Conclusion: Taking into consideration the fact that the advantages of increased life expectancy will achieved only if these extra years of life gained through increased longevity are spent in good health, the importance of conducting additional research on gender differences is more than evident, particularly in terms of providing meaningful insight into the development of action plans devised to deal with gender differences in health status, simultaneously promoting healthy and active aging for both men and women.
Keywords: self-reported health status; elderly; gender; national health survey